Prognostic significance of preoperative neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in patients with glioma - Wang, Junli; Xiao, Wenjing; Chen, Wanyi; Hu, Yonghe (Technische Universität Dortmund, 2018)
The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been recognized as inflammatory markers and used as prognostic makers in various cancers. The present study sought to investigate the prognostic role of NLR and PLR in Chinese patients with glioma. Clinical data, including NLR, PLR and overall survival (OS), were collected from 112 patients who underwent surgery to treat primary glioma. Kaplan-Meier survival analysis as well as uni- and multivariate Cox regression were performed to examine potential associations of preoperative NLR and PLR with OS. Among all patients, mean NLR was 3.80±1.48 and mean PLR was 183.60 ±81.38. NLR increased with increasing WHO tumor grade (p < 0.05), but PLR did not (p > 0.05). Patients with NLR ≥ 4 had significantly shorter mean OS (20.75±7.68 months) than patients with NLR < 4 (26.91±7.50 months; p < 0.001). Similarly, patients with PLR ≥ LR had significantly shorter OS than patients with PLR < 200 (p = 0.007). Univariate Cox analysis identified the following parameters as significantly associated with worse OS: NLR (≥ 4), PLR (> 200), tumor size (≥ 5 cm), WHO grade (III/IV), and Karnofsky Performance Status (< 70). Multivariate analysis identified only NLR > 4 as an independent predictor of OS (HR 1.932, 95 % CI 1.011 to 3.694, p = 0.046). Our results suggest that at least in Chinese patients, increased preoperative NLR and PLR are associated with worse OS, and NLR may be an independent risk factor to identify glioma patients with poor prognosis. These results should be validated and extended in larger clinical studies.
EXCLI Journal;Vol. 17 2018
Keywords: Glioma; Neutrophil to lymphocyte ratio; Platelet to lymphocyte ratio; Prognosis; 610